Praktik Diskursif dan Pengembangan Pengetahuan Mahasiswa dalam Pembelajaran Sejarah (Universitas Negeri Semarang, 2023)
This study aims to develop students' tolerance knowledge. The research question is: how do students construct tolerance knowledge? and what are the main factors influencing student acceptance of the idea of tolerance? This research was carried out using qualitative methods with a grounded research framework, the focus of this study was on classroom management, language use practices and student authority in developing tolerance knowledge. This research involved students from various backgrounds. Analysis of the research data using Critical Discourse Analysis (CDA). The results of this study indicate that discursive practice can be a stimulus for the development of students' tolerance knowledge in history classes. The main factors that encourage student acceptance of tolerance knowledge are nationalism, Pancasila ideology, acceptance of differences, and historical reasons. Multicultural classroom management using a humanistic approach produces thinking constructions of students who are tolerant and able to deal with the threats and impacts of intolerance practices in society. The implication of this research is that learning history needs to utilize actual and contextual learning resources in developing tolerance knowledge and preparing students to become agents of tolerance in society who are ready to face the threats and impacts of intolerance practices.